2009
DOI: 10.1177/0961000609337093
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Lines of Communication

Abstract: Changes in library and information professional communications and journal publication in the last two decades are considered. Journals of professional bodies such as the Library Association and Aslib have now been sold to commercial publishers. The emergence of electronic journals is exemplified. Electronic discussion lists and newer forms of interactive communication, e.g. blogs and social networking sites, are discussed. The time spent in accessing and using e-sources of professional information should lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ten studies tried to identify and measure the impact that Twitter has on libraries and reported their findings. Dudley (2009) argued that SNSs, such as blogs and Twitter among others, have changed the electronic discussion lists and online communication. Carscaddon and Harris (2009) argued that Twitter helped in overcoming information overload, as friends and subscribers can be seen as filters to credible information.…”
Section: Twitter's Impact On Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies tried to identify and measure the impact that Twitter has on libraries and reported their findings. Dudley (2009) argued that SNSs, such as blogs and Twitter among others, have changed the electronic discussion lists and online communication. Carscaddon and Harris (2009) argued that Twitter helped in overcoming information overload, as friends and subscribers can be seen as filters to credible information.…”
Section: Twitter's Impact On Librariesmentioning
confidence: 99%
“…As any new technology or development, Twitter affected different aspects of libraries. In particular, it was found that libraries' use of Twitter had an impact on the way the discussion was conducted in an online environment; online privacy; overcoming information overload; the emergence of new online communities; and, finally, library marketing policy (Carscaddon and Harris, 2009;Dudley, 2009;Griffey, 2010;Rainie, 2010b;Stuart, 2013). As a result, there is a growing need for librarians to adopt new roles to live up to user's expectations for innovative ways of communication and access to information.…”
mentioning
confidence: 99%